Effectiveness of E-wallet Transactions in a Small Business Enterprise in Batasan Hills, Quezon City: Developing a Guidelines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
From the results of this study, the effectiveness of E-wallet transactions in a small businessenterprise in Batasan Hills Quezon City In terms of Transaction, Payment accessibility,Convenience, Portability, and Security Privacy are "Extremely Effective" as determinants forthe effectiveness of E-wallet transaction in a small business enterprise in Batasan HillsQuezon City. The problems encountered by Small Business enterprises in Batasan HillsQuezon City revealed that the biggest problems encountered were: E-wallet apps require aninternet connection, which limits customer transactions using the e-wallet app; E-wallet appsupdate, maintenance frequently delay payment transactions, And E-wallet may not beacceptable or compatible everywhere the business struggles when their customer who used e-wallet is not compatible to their transaction method.This study recommended that the small business enterprise in Batasan Hills Quezon Cityshould focus on improving the necessary procedure to maintain the effectiveness of E-wallettransactions by determining the factors that need to be considered in the effects of E-wallettransactions in terms of Payment accessibility, Convenience, Portability and Security andPrivacy Based on the findings, the researchers propose a guidelines.
Keywords: Business